Bacterial RNA virus MS2 exposure increases the expression of cancer progression genes in the LNCaP prostate cancer cell line - Sanmukh, Swapnil Ganesh [UNESP] (2023)
Bacteriophages effectively counteract diverse bacterial infections, and their ability to treat most types of cancer has been explored using phage engineering or phage-virus hybrid platforms. In the present study, it was demonstrated that the bacteriophage MS2 can affect the expression of genes associated with the proliferation and survival of LNCaP prostate epithelial cells. LNCaP cells were exposed to bacteriophage MS2 at a concentration of 1x10(7) plaque forming units/ml for 24-48 h. After exposure, various cellular parameters, including cell viability, morphology, and changes in gene expression, were examined. MS2 affected cell viability adversely, reducing viability by 25% in the first 4 h of treatment; however, cell viability recovered within 24-48 h. Similarly, the AKT, androgen receptor, integrin alpha 5, integrin beta 1, MAPK1, MAPK3, STAT3, and peroxisome proliferator-activated receptor-gamma coactivator 1 alpha genes, which are involved in various normal cellular processes and tumor progression, were significantly upregulated, whereas the expression levels of HSP90, ITGB5, ITGB3, HSP27, ITGAV, and PI3K genes were unchanged. Therefore, based on viability and gene expression changes, bacteriophage MS2 severely impaired LNCaP cells by reducing anchorage-dependent survival and androgen signaling. A caveolin-mediated endocytosis mechanism for MS2-mediated signaling in prostate cancer cells was proposed based on reports involving bacteriophages T4, M13, and MS2, and their interactions with LNCaP and PC3 cell lines.